Influence of polyamines of bacterial origin on the production of key cytokines in the culture of human mononuclear leukocytes - A. P. Godovalov; T. I. Karpunina (Медицинская иммунология, 2022)
To date, participation of biogenic polyamines has been studied in details, with respect to regulation of microbial gene expression, interrelations between bacteria, development of their persistence state. Opportunity of their use as markers of human pathological conditions is being actively evaluated. The aim of our study was to assess the effect of bacterial diamines, i.e., cadaverine and putrescine, upon production of key cytokines (IFNγ and IL-4) in the culture of human mononuclear leukocytes. We studied leukocytes of peripheral venous blood obtained from 18 healthy male volunteers (mean age 24.0±0.6 years). The leukocytes were isolated by means of gradient centrifugation using a Ficoll-Verografin mixture. For the cultivation of lymphocytes, a micro-method and plastic round-bottom 96-well plates were used. Concanavalin A at a concentration of 5 μg/ml was used as a T cell mitogen. Polyamines were used at final concentrations of 5, 25, 50, 75 and 100 μM/L. The cultivation was carried out in humidified atmosphere with 5% CO2, at 37 °C for 72 hours. At the end of incubation, the culture medium was collected and frozen for subsequent quantitative enzyme immunoassays of cytokine concentrations (IFNγ and IL-4) (Russia). Viable cells were counted using Goryaev chamber after staining with 0.1% trypan blue solution. Statistical analysis was performed using Student’s t test or Mann–Whitney test. Addition of cadaverine at all concentrations reduced IFNγ production in the culture of mitogen-activated cells. When culturing leukocytes supplied with putrescine (5 to 50 μM/L), a dose-dependent decrease of IFNγ was observed. Upon further increase of putrescine concentrations, the IFNγ production is restored to the values of the control samples. Direct toxic effect of polyamines upon the cells was revealed. Both the diamines, at the doses of 50, 75, and 100 μM/L, caused increase of IL-4 production by the mitogen-activated cells. Such changes can be associated both with direct cytotoxic effect of cadaverine and putrescine, being mediated by changes of some metabolic pathways. In addition, the effects of polyamines upon monocytes present in culture can include their anti-inflammatory state, e.c., an increased IL-4 production. In general, cadaverine and putrescine, produced by microorganisms of various taxonomic groups, regulate the effectiveness of compensatory-adaptive reactions that ensure adaptation of microbial populations to changing or unfavorable environmental conditions.